The introduction of a GMI scheme in Cyprus: Family structure, equivalence scales and policy challenges - Christos Koutsampelas (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Nowadays, Cyprus has engaged in an effort of reforming its tax-benefit system so as to adapt to the economic and social challenges of the post-crisis era. Among the most important social reforms is the introduction of a Guaranteed Minimum Income scheme (GMI). In this paper, we construct a number of hypothetical reform scenarios using the EUROMOD microsimulation model aiming at examining how certain features of the policy design affect the policy outcomes of the reform. The empirical analysis is accompanied with a wider discussion of the driving forces of the reform and the challenges which policymakers are expected to confront when implementing the new welfare scheme in the particular context of Cyprus.
Keywords: I38; I32; 330; EUROMOD; Guaranteed Minimum Income; Cyprus